1999
DOI: 10.1002/(sici)1096-9861(19990428)407:1<33::aid-cne3>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of subtype 4a metabotropic glutamate receptors in the rat and mouse basal ganglia

Abstract: Recent studies suggest that metabotropic glutamate receptors (mGluRs) may play a significant role in regulating basal ganglia functions. In this study, we investigated the localization of mGluR4a protein in the mouse and rat basal ganglia. Polyclonal antibodies that specifically react with the metabotropic glutamate receptor subtype mGluR4a were produced and characterized by Western blot analysis. These antibodies recognized a native protein in wild‐type mouse brain with a molecular weight similar to the molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
79
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(95 citation statements)
references
References 32 publications
6
79
0
Order By: Relevance
“…This view is consistent with our studies of electrically evoked postsynaptic potentials that were decreased in amplitude by activation of mGluRs, coupled with the absence of any modulation of postsynaptic responses to ionotropic glutamate receptor agonists. That mGluRs are located on presynaptic terminals is consistent both with previous electrophysiological (Schrader and Tasker, 1997;Evans et al, 2000;Awatramani and Slaughter, 2001) and immunocytochemical (Bradley et al, 1996(Bradley et al, , 1999Shigemoto et al, 1997) studies of other neuronal types.…”
Section: Site Of Mglur Actionsupporting
confidence: 89%
See 2 more Smart Citations
“…This view is consistent with our studies of electrically evoked postsynaptic potentials that were decreased in amplitude by activation of mGluRs, coupled with the absence of any modulation of postsynaptic responses to ionotropic glutamate receptor agonists. That mGluRs are located on presynaptic terminals is consistent both with previous electrophysiological (Schrader and Tasker, 1997;Evans et al, 2000;Awatramani and Slaughter, 2001) and immunocytochemical (Bradley et al, 1996(Bradley et al, , 1999Shigemoto et al, 1997) studies of other neuronal types.…”
Section: Site Of Mglur Actionsupporting
confidence: 89%
“…Anatomical and electrophysiological studies have shown that group III mGluRs can be located presynaptically or postsynaptically on different neurons (Martin et al, 1997;Shigemoto et al, 1997;Bradley et al, 1999;Taverna and Pennartz, 2003). To examine the site of action of the metabotropic group III agonist L-AP-4 in hypocretin neurons, we further studied its effect on the amplitude and frequency of miniature EPSCs (mEPSCs).…”
Section: Presynaptic Effects Of L-ap-4 On Excitatory Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…are linked to the activation of phospholipase C and generally mediate postsynaptic excitatory effects, whereas group II (mGluR2 and -3) and group III (mGluR4, receptors are negatively coupled to adenylyl cyclase and generally mediate presynaptic inhibitory influences on neurotransmitter release (Nakanishi, 1994;Conn and Pin, 1997) The basal ganglia are enriched in the three groups of mGluRs, but current knowledge of their synaptic localization and functions remains limited. In the striatum, group I mGluRs are primarily expressed in projection neurons and subpopulations of interneurons, whereas group II and III mGluRs are mostly localized presynaptically on glutamatergic terminals (Testa et al, 1994(Testa et al, , 1995(Testa et al, , 1998Kinoshita et al, 1998;Bradley et al, 1999;Kosinki et al, 1999;Tamaru et al, 2001;Corti et al, 2002). In addition to their preponderance in postsynaptic striatal neurons, activation of group I mGluRs also mediates presynaptic effects on GABA and dopamine release in the rat striatum (Verma and Moghaddam, 1998;Bruton et al, 1999;Battaglia et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…1). With the exception of mGluR6, which is localized postsynaptically in cells of the retina, the other Group III mGluRs show primarily a presynaptic localization (3,4), although at some synapses these receptors may also be present postsynaptically. Presynaptic Group III mGluRs act as autoreceptors to inhibit the release of L-glutamate from glutamatergic nerve terminals (4 -6), and ␥-aminobutyric acid release via glutamate spillover onto GABAergic synapses expressing mGluRs (7).…”
mentioning
confidence: 99%